The Influence of Leadership, Work Environment and Work Discipline on Job Satisfaction - sulis tri wahyuni (Universitas Trunodjoyo Madura, 2025)
The purpose of this study was to analyze the influence of leadership, work environment and work discipline on job satisfaction at the Environmental and Forestry Service of the Special Region of Yogyakarta. This study uses a quantitative approach by collecting data using a questionnaire. The population in this study were 77 employees of the main service at the Environmental and Forestry Service of the Special Region of Yogyakarta. The sampling technique in this study used nonprobability sampling, namely by using saturated sampling. Data were analyzed using IBM SPSS Statistics version 25 to see and test the relationship between variables. The results of the partial analysis of this study indicate that Leadership has a positive and significant effect on Job Satisfaction, Work Environment has a positive and significant effect on Job Satisfaction, Work Discipline has a negative effect and there is no significant effect on Job Satisfaction. Simultaneously shows that Leadership, Work Environment and Work Discipline have a positive and significant effect on Job Satisfaction.